Avaliação da expressão do mRNA dos genes Ataxia Telangiectasia Mutadae Ataxia Telangiectasia RAD-3 relacionada em pacientes com síndrome mielodisplásica - Castro, Marilena Facundo (2017)
Several factors are involved in the pathogenesis of Myelodysplastic Syndrome, e.g. genetic instability that may be caused by ineffective activation of DNA repair mechanisms. The ataxia-telangiectasia mutated (ATM) and ataxia-telangiectasia mutated and Rad-3-related (ATR) proteins kinases act as central regulators of the DNA damage response. The aim of this study was to evaluate the relationship between gene expression and the epidemiological, clinical, and laboratory characteristics of patients with MDS. We evaluated the expression of ATM and ATR genes by quantitative PCR methods. The results of expression were related with different clinical variables using the SPSS 21.0 software. The survival analyzes were performed using the Cutoff Finder software. The results showed that the hypo expression of the ATM and ATR repair genes was related to patients with hypocellular bone marrow (p=0.021 and p=0.002respectively), in neutropenia (p=0.019 and p=0.032 respectively) and in the presence of 2 or 3 cytopenias (p= 0.012 and p=0.002,respectively). Hypoexpression was also observed for the ATM gene in the presence of dysgranulopoesis (p=0.01). The increase of the ATR gene expression was observed in patients who progressed to acute myeloid leukemia (p=0.005) and analyzes of overall and AML-free survival showed that the increase in ATR was associated with a worse overall survival (p=0.0001) and the increased risk of progression to AML (p=0.0029).In addition, ATM and ATR are strongly correlated (r²=0.560 and p=0.000).We concluded that hypo expression of the ATM and ATR genes is related to hypoplastic MDS and that hypo expression is related to the accumulation of damage and possible involvement of the cell lines. In addition, DNA repair genes are strongly correlated to MDS and that the ATR hyperexpression is related to the risk of progression to AML and worse overall survival.